The Effectiveness Level of Gel Combination Binahong Leaf and Turmeric Rhizome Extract on The Mature Collagen of IIB Degree Burns in Rats - Suryaningtyas, Ignasia Friska Amelia; Rachmawati, Kadek; Lukiswanto, Bambang Sektiari; Sudjarwo, Sri Agus; Soeharsono; Yuniarti, Wiwik Misaco (Universitas Airlangga, 2023)
The aim of this research was to evaluate the effect of administering a combination gel of binahong leaf and turmeric rhizome extracts on mature collagen of IIB degree Burns in rat. A total of 25 male rats, 3 months of age, 150-200 gram body weight were used. This research consists of five treatments. P0 were normal skin, P1 were used 1% silver sulfadiazine, P2, P3, and P4 were gel combination of binahong leaf and turmeric rhizome extracts with increase concentration of binahong leaf extract i.e. 1.25%, 2.5%, and 5%, while turmeric rhizome extract i. e 2% for each treatment. Treatments have been given topically for 14 days, twice a day, started after burn wound application. At the end of the treatment period, skin excision was carried out, then the histopathological examination was performed. Microscopic observation on the wound healing process on mature collagen density showed that P0 was not a significant difference with P3 and P4, but P0 was significant difference with P1 and P2. The better burn healing process on P3 is allegedly because of the activity of saponin, and tannin, contained in the binahong leaf extract 2.5%, and curcumin in turmeric rhizome extract 2% have been proven to be effective for topical burns therapy.